Effect of ambulatory versus hospital treatment for gestational diabetes or hyperglycemia on infant mortality rates: a systematic review - Rudge, Marilza Vieira Cunha; Lima, Silvana Andréa Molina; Dib, Regina Paolucci El; Marini, Gabriela; Magalhães, Claudia; Calderon, Iracema de Mattos Paranhos (São Paulo Medical Journal, 2013)
CONTEXT AND OBJECTIVE: Pregnancies complicated by diabetes are associated with increased neonatal and maternal complications. The most serious maternal complication is the risk of developing type 2 diabetes, 10-12 years after the delivery. For rigorous control over blood glucose, pregnant women are treated through ambulatory management or hospitalization. The aim of this study was to evaluate the effectiveness of ambulatory management versus hospitalization in pregnancies complicated by diabetes or hyperglycemia. DESIGN AND SETTING: Systematic review conducted in a public university hospital. METHODS: A systematic review of the literature was performed and the main electronic databases were searched. The date of the most recent search was September 4, 2011. Two authors independently selected relevant clinical trials, assessed their methodological quality and extracted data. RESULTS: Only three studies were selected, with small sample sizes. There was no statistically significance different between ambulatory management and hospitalization, regarding mortality in any of the subcategories analyzed: perinatal and neonatal deaths (relative risk [RR] 0.65; 95% confidential interval [CI]: 0.11 to 3.84; P = 0.63); neonatal deaths (RR 0.29; 95% CI: 0.01 to 6.07; P = 0.43); and infant deaths (RR 0.29; 95% CI: 0.01 to 6.07; P = 0.43). CONCLUSIONS: This review, based on studies with high or moderate risk of bias, showed that there was no statistically significant difference between ambulatory management and hospital care, regarding reduction of mortality rates in pregnancies complicated by diabetes or hyperglycemia. It also suggested that there is a need for further randomized controlled trials on this issue.